Aplikasi Teknologi Dna Untuk Akselerasi Program Pemuliaan Ketahanan Tanaman Kakao Terhadap Hama Dan Penyakit Utama - I Made Tasma (Badan Penelitian dan Pengembangan Pertanian, 2016)
ABSTRACTOne of the main constraints on cacao cultivation is disease and insect pest attacks causing significant yield loss. The main insect pests and diseases on cacao plantation are cacao pod borer, cacaofruit rot, vascular streak dieback and cacao mirids (Helopeltis spp.). Conventional breeding method to obtain new cacao clones resistant to insect pests and diseases is a slow process. It may take 15-20 years to obtain a new superior clone. Applying DNA technology should expedite cacao breeding program. The article described the application of DNA technology currently available to expedite cacao breeding program for disease and insect resistance. Many genes and quantitative trait loci (QTLs) of important traits have been discovered related to cacao plant productivity and yield quality, disease and insect pest resistance traits. Modern genomic technologies as well as DNA marker have also been applied in cacao breeding program. Genetic transformation technology has been explored its application for cacao improvement. With the development of modern genomic technology, important gene/QTL discoveries would be faster to accelerate insect pest and disease resistant cultivar development. All these new DNA technologies have been assessed their potential applications for coping important pest and disease and for yield improvement. DNA technologies, mainly MAS and genomic-data based breeding technologies are ready to be applied to support breeding programs for main pest and disease resistance to enhance Indonesian cacao productivity and quality.Keywords: Cacao, disease and insect resistance, genomics, DNA markers, genetic transformation, marker-assisted breedingAbstrakSalah satu kendala utama dalam budi daya kakao ialah serangan hama dan penyakit. Hama dan penyakit utama kakao adalah penggerek buah kakao (PBK), busuk buah kakao (BBK), vascular streak dieback (VSD), dan cacao mirids (Helopeltis spp.). Kegiatan pemuliaan tanaman kakao secara konvensional berjalan lambat dan perlu waktu panjang. Untuk menghasilkan satu varietas unggul diperlukan waktu 15-20 tahun. Aplikasi teknologi DNA (genomika melalui pemuliaan berbantuan marka dan rekayasa genetik) dapat mempercepat program pemuliaan tanaman kakao. Tulisan ini mengulas teknologi DNA yang tersedia saat ini dan potensi aplikasinya untuk mempercepat pemuliaan kakao tahan hama dan penyakit. Penemuan marka DNA dan gen/quantitative trait loci (QTL) kakao berkembang cukup pesat. Banyak gen dan QTL karakter penting telah diidentifikasi yang terkait ketahanan hama dan penyakit serta produktivitas tanaman. Teknologi genomika dan pemanfaatan teknik marker-assisted selection (MAS) juga telah diaplikasikan untuk pemuliaan kakao termasuk untuk karakter ketahanan terhadap hama dan penyakit. Teknologi rekayasa genetik telah diteliti untuk menganalisis potensi pemanfaatannya dalam perbaikan bahan tanam kakao. Dengan berkembangnya teknologi genomika modern, penemuan gen/QTL unggul dapat dipercepat, lebih efisien dan komprehensif untuk mempercepat perakitan varietas unggul kakao tahan hama dan penyakit. Teknologi DNA khususnya MAS dan pemuliaan berbasis data genom siap diaplikasikan untuk mendukung program perbaikan ketahanan tanaman kakao terhadap hama dan penyakit utama dalam rangka peningkatan produktivitas dan mutu kakao nasional.